Trends and Determinants of Financial Distress: Evidence from Two-Decade Studies - Rahayu, Nur Ellyanawati Esty; Kusuma, Hadri; Arifin, Zaenal (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study maps trends and developments in financial distress research on publicly listed firms, highlighting themes, methods, and contexts to expose gaps for future work. Its contribution lies in offering a systematic, mixed-method review covering two decades of studies (2004–2024), which clarifies how the field has evolved and where it must advance. Articles were retrieved through Publish or Perish using the Scopus database, yielding insights into dominant themes of financial performance, corporate governance, and ownership structure. Current discourse gravitates around financial distress as a broad phenomenon, its occurrence in listed companies, and country-specific contexts. Looking forward, research opportunities cluster around financial distress prediction, turnaround strategies, and comparative country evidence. The findings equip scholars and practitioners with a structured view of existing knowledge while guiding targeted inquiry, ensuring future studies address pressing blind spots and enhance the practical utility of financial distress scholarship.